Obstructive Sleep Apnea and Body Weight - Browman, Carl P. (1984)
A patient with obstructive sleep apnea was monitored five times during three years while his weight fluctuated within a range of 26 kg. The number of apneas per hour of sleep varied from 59.6 at 111 kg of weight to 3.1 at 85 kg. The relation between apneas per hour of sleep and body weight was a logarithmic function. A modest decrease in weight was thus associated with a disproportionally larger decrease in the rate of apneas. Typical SaO(2) levels during the apneic episodes also had a logarithmic relation with body weight. Apnea-related sinus bradycardia and sinus tachycardia were only present at the highest weight. The results suggested that dieting and weight loss lead to an improvement in sleep apnea and related sequelae.